Electrostatic image developing toner, electrostatic image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
Patent Information
- Application Number
- CN202110180888.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-23
- Filing Date
- 2021-02-07
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2041-02-07
AI Technical Summary
[0036]根据上述第3方案,提供一种静电图像显影用色调剂,与Net强度NCa大于3.00kcps的静电图像显影用色调剂相比,该方案的静电图像显影用色调剂向含水量比较多的记录介质上的转印性优异。
Smart Images

Figure CN114253096B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to toners for electrostatic image development, electrostatic image developers, toner cartridges, processing cartridges, image forming apparatus, and image forming methods. Background Technology
[0002] Japanese Patent No. 4657932 discloses a colorant for image forming, which includes an adhesive resin and a colorant. 50 to 100% by weight of the adhesive resin is polyester resin. The colorant is a masterbatch made by mixing a pigment with an acidic surface treatment, a dispersant, and the adhesive resin. The dispersant has an acid value of 1 to 30 mg KOH / g or less and an amine value of 1 to 100 or more. CI pigment red 57:1 is used as one of the colorants.
[0003] Japanese Patent Application Publication No. 2019-040024 discloses a colorant comprising colorant particles having a colorant core and a shell. The colorant core contains a melt blend of an amorphous resin and a crystalline resin, and the shell contains a thermosetting resin. The melt blend contains two or more crystalline resin microdomains, and among the two or more crystalline resin microdomains, the proportion of microdomains that meet the conditions of a minor axis diameter of 50 nm or more and 200 nm or less and an aspect ratio of 4.0 or more and 20.0 or less is 80% or more.
[0004] Japanese Patent Application Publication No. 2017-003990 discloses a colorant comprising colorant particles containing an amorphous polyester resin, a crystalline polyester resin, and a wax, wherein wax microdomains and crystalline polyester resin crystals are present. In the cross-sectional area of the colorant, the area occupied by the wax microdomains is 0.5% to 8.0%, the area occupied by the crystalline polyester resin crystals is 0.5% to 8.0%, the average diameter of the number of wax microdomains is 60 nm to 240 nm, the aspect ratio of the crystalline polyester resin crystals is 5.0 to 25.0, and the average diameter of the number of long axis lengths of the crystalline polyester resin crystals is 0.8 to 2.0 times the average diameter of the number of wax microdomains. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a toner for electrostatic image development, wherein the net intensity N of Mg element contained in amorphous polyester resin, crystalline polyester resin and CI pigment red 57:1 is determined by fluorescence X-ray analysis. Mg Compared to electrostatic image developing toners with a viscosity of less than 0.10 kcps, the electrostatic image developing toner provided by this invention exhibits superior transferability to recording media with high water content.
[0006] According to a first aspect of the present invention, a toner for electrostatic image development is provided, comprising an amorphous polyester resin, a crystalline polyester resin, and CI pigment red 57:1, wherein the net intensity N of Mg element is determined by fluorescence X-ray analysis. Mg It is between 0.10 kcps and 0.40 kcps.
[0007] In the second aspect of the present invention, the aforementioned Net strength N Mg The range is between 0.15 kcps and 0.35 kcps.
[0008] According to the third aspect of the present invention, the Net intensity N of Ca element is determined by fluorescence X-ray analysis. Ca The range is between 1.00 kcps and 3.00 kcps.
[0009] According to the fourth aspect of the present invention, the above-mentioned Net strength N Ca The range is between 1.20 kcps and 2.50 kcps.
[0010] According to the fifth aspect of the present invention, the Net intensity N of Cl element is determined by fluorescence X-ray analysis. Cl The range is between 0.50 kcps and 2.00 kcps.
[0011] According to the sixth aspect of the present invention, the above-mentioned Net strength N Cl It is between 0.70 kcps and 1.80 kcps.
[0012] According to the seventh aspect of the present invention, the Net intensity N of Ca element is determined by fluorescence X-ray analysis. Ca The Net intensity (N) of Mg element determined by fluorescence X-ray diffraction. Mg And the Net intensity N of Cl element determined by fluorescence X-ray analysis Cl Satisfying 0.50≦(N) Mg +N Cl ) / N Ca A relationship of ≤1.50.
[0013] According to the eighth aspect of the present invention, the above-mentioned Net strength N Ca The above Net strength N Mg And the aforementioned Net strength N Cl Satisfying 0.80≦(N) Mg +N Cl ) / N Ca The relationship is ≤1.30.
[0014] According to the ninth aspect of the present invention, the above-mentioned electrostatic image developing toner further contains a release agent, the release agent comprising an ester compound formed between a higher fatty acid having 10 to 25 carbon atoms and a mono- or polyol.
[0015] According to the tenth aspect of the present invention, the colorant particles have the following characteristics: when the cross-section of the colorant particles is observed, at least two crystalline resin microregions satisfy the following conditions (A), (B1), (C), and (D).
[0016] Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower.
[0017] Condition (B1): The major axis length of the crystalline resin microregion is 0.5 μm or more and 1.5 μm or less.
[0018] Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent described below is more than 60 degrees and less than 90 degrees. The tangent is the tangent at the junction where the extension meets the surface of the colorant particles.
[0019] Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.
[0020] According to the 11th aspect of the present invention, the colorant particles have the following characteristics: when the cross-section of the colorant particles is observed, at least two crystalline resin microregions satisfy the following conditions (A), (B2), (C), and (D).
[0021] Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower.
[0022] Condition (B2): The ratio of the major axis length of the crystalline resin microregion in at least one of the two crystalline resin microregions to the maximum diameter of the colorant particle is more than 10% and less than 30%.
[0023] Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent described below is more than 60 degrees and less than 90 degrees. The tangent is the tangent at the junction where the extension meets the surface of the colorant particles.
[0024] Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.
[0025] According to the 12th aspect of the present invention, the toner particles contain a release agent, and when the cross-section of the toner particles is observed, the micro-regions of the release agent exist inside at a depth of 50 nm or more from the surface of the toner particles.
[0026] According to the 13th aspect of the present invention, the content of the above-mentioned colorant particles is 40% or more relative to all colorant particles.
[0027] According to the 14th aspect of the present invention, the content of the above-mentioned colorant particles is 70% or more relative to all colorant particles.
[0028] According to a 15th aspect of the present invention, an electrostatic image developer is provided, which comprises the above-mentioned electrostatic image developing toner.
[0029] According to the 16th aspect of the present invention, a toner cartridge that is loaded and unloaded in an image forming apparatus is provided, which stores the aforementioned toner for electrostatic image development.
[0030] According to a 17th aspect of the present invention, a processing cartridge that is loaded and unloaded in an image forming apparatus is provided, which includes a developing mechanism that stores the electrostatic image developer and uses the electrostatic image developer to develop an electrostatic image formed on the surface of an image holder into a toner image.
[0031] According to an 18th aspect of the present invention, an image forming apparatus is provided, comprising: an image holder; a charging mechanism for charging the surface of the image holder; an electrostatic image forming mechanism for forming an electrostatic image on the charged surface of the image holder; a developing mechanism for storing the electrostatic image developer and developing the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer mechanism for transferring the toner image formed on the surface of the image holder to a surface of a recording medium; and a fixing mechanism for fixing the toner image transferred to the surface of the recording medium.
[0032] According to a 19th aspect of the present invention, an image forming method is provided, comprising the following steps: a charging step, charging an image holder surface; an electrostatic image forming step, forming an electrostatic image on the charged image holder surface; a developing step, developing the electrostatic image formed on the image holder surface into a toner image using the electrostatic image developer; a transfer step, transferring the toner image formed on the image holder surface to a recording medium surface; and a fixing step, fixing the toner image transferred to the recording medium surface.
[0033] (Effect)
[0034] According to the first embodiment above, a colorant for electrostatic image development is provided, comprising an amorphous polyester resin, a crystalline polyester resin, and CI pigment red 57:1, and a Net intensity N. MgCompared to electrostatic image developing toners with a viscosity of less than 0.10 kcps, the electrostatic image developing toner of this scheme exhibits superior transferability onto recording media with higher water content.
[0035] According to the second embodiment above, a colorant for electrostatic image development is provided, comprising an amorphous polyester resin, a crystalline polyester resin, and CI pigment red 57:1, and a Net intensity N. Mg Compared to electrostatic image developing toners with a viscosity of less than 0.15 kcps, the electrostatic image developing toner of this scheme exhibits superior transferability onto recording media with higher water content.
[0036] According to the third scheme described above, a colorant for electrostatic image development is provided, which is related to the Net intensity N. Ca Compared to electrostatic image developing toners with a viscosity greater than 3.00 kcps, the electrostatic image developing toner of this scheme exhibits superior transferability onto recording media with higher water content.
[0037] According to the fourth scheme described above, a colorant for electrostatic image development is provided, which is related to the Net intensity N. Ca Compared to electrostatic image developing toners with a viscosity greater than 2.50 kcps, the electrostatic image developing toner of this scheme exhibits superior transferability onto recording media with higher water content.
[0038] According to the fifth scheme described above, a colorant for electrostatic image development is provided, which is related to the Net intensity N. Cl Compared to electrostatic image developing toners with a viscosity of less than 0.50 kcps, the electrostatic image developing toner of this scheme exhibits superior transferability onto recording media with higher water content.
[0039] According to the sixth scheme described above, a colorant for electrostatic image development is provided, which is related to the Net intensity N. Cl Compared to electrostatic image developing toners with a viscosity of less than 0.70 kcps, the electrostatic image developing toner of this scheme exhibits superior transferability onto recording media with higher water content.
[0040] According to the seventh embodiment above, a colorant for electrostatic image development is provided, which is compatible with (N) Mg +N Cl ) / N Ca Compared to electrostatic image developing toners with a concentration less than 0.50, the electrostatic image developing toner of this scheme exhibits superior transferability onto recording media with higher water content.
[0041] According to the eighth embodiment above, a colorant for electrostatic image development is provided, which is compatible with (N) Mg +N Cl ) / N CaCompared to electrostatic image developing toners with a value less than 0.80, the electrostatic image developing toner of this scheme exhibits superior transferability onto recording media with higher water content.
[0042] According to the above-mentioned ninth embodiment, an electrostatic image developing tone agent is provided, which, compared with the form of release agent that does not contain ester wax, exhibits excellent transferability to recording media with high water content.
[0043] According to the above-mentioned 10th scheme, an electrostatic image developing toner is provided, which has excellent transferability to recording media with high water content compared with an electrostatic image developing toner that does not have toner particles that satisfy conditions (A), (B1), (C), and (D).
[0044] According to the above-mentioned 11th scheme, an electrostatic image developing tone agent is provided, which has excellent transferability to recording media with high water content compared with an electrostatic image developing tone agent that does not have tone agent particles that satisfy conditions (A), (B2), (C), and (D).
[0045] According to the above-mentioned 12th scheme, an electrostatic image developing tone agent is provided. Compared with an electrostatic image developing tone agent in which the micro-region of the release agent exists in the surface layer at a depth of less than 50 nm from the surface of the tone agent particles, the electrostatic image developing tone agent of this scheme has excellent transferability to recording media with a high water content.
[0046] According to the above-mentioned 13th scheme, an electrostatic image developing tone agent is provided, which has superior transferability to recording media with high water content compared with electrostatic image developing tone agents that meet conditions (A), (B1), (C), and (D) where the content of tone agent particles is less than 40% of the total number of tone agent particles, or compared with electrostatic image developing tone agents that meet conditions (A), (B2), (C), and (D) where the content of tone agent particles is less than 40% of the total number of tone agent particles.
[0047] According to the above-mentioned 14th scheme, an electrostatic image developing tone agent is provided, which has superior transferability to recording media with high water content compared with electrostatic image developing tone agents that meet conditions (A), (B1), (C), and (D) where the content of tone agent particles is less than 70% of the total number of tone agent particles, or compared with electrostatic image developing tone agents that meet conditions (A), (B2), (C), and (D) where the content of tone agent particles is less than 70% of the total number of tone agent particles.
[0048] According to the aforementioned 15th embodiment, an electrostatic image developer is provided, comprising a Net intensity N of Mg element containing amorphous polyester resin, crystalline polyester resin, and CI Pigment Red 57:1, as determined by fluorescence X-ray analysis. Mg Compared to electrostatic image developers with toners of less than 0.10 kcps, the electrostatic image developer of this scheme exhibits superior transfer properties onto recording media with higher water content.
[0049] According to the 16th embodiment above, a colorant cartridge is provided, which stores the Net intensity N of Mg element contained in amorphous polyester resin, crystalline polyester resin and CI Pigment Red 57:1, and determined by fluorescence X-ray analysis. Mg Compared to toner cartridges for electrostatic image development with a toner concentration of less than 0.10 kcps, the toner cartridge of this scheme exhibits superior transfer performance onto recording media with higher water content.
[0050] According to the 17th embodiment described above, a processing cartridge is provided that, compared to a processing cartridge storing an electrostatic image developer, exhibits superior transferability to recording media with high water content. The electrostatic image developer contains an amorphous polyester resin, a crystalline polyester resin, and CI Pigment Red 57:1, and the Net intensity N of Mg element is determined by fluorescence X-ray analysis. Mg Toner for developing electrostatic images with a viscosity of less than 0.10 kcps.
[0051] According to the 18th embodiment described above, an image forming apparatus is provided that, compared to an image forming apparatus that stores an electrostatic image developer in a developing mechanism, exhibits superior transfer performance onto recording media with high water content. The electrostatic image developer contains an amorphous polyester resin, a crystalline polyester resin, and CI Pigment Red 57:1, and the Net intensity N of Mg element is determined by fluorescence X-ray analysis. Mg Toner for developing electrostatic images with a viscosity of less than 0.10 kcps.
[0052] According to the aforementioned 19th embodiment, an image forming method is provided that, compared to an image forming method using an electrostatic image developer in the developing step, exhibits superior transferability to recording media with high water content. This electrostatic image developer contains an amorphous polyester resin, a crystalline polyester resin, and CI Pigment Red 57:1, and the Net intensity N of Mg element is determined by fluorescence X-ray analysis. Mg Toner for developing electrostatic images with a viscosity of less than 0.10 kcps. Attached Figure Description
[0053] Figure 1This is a schematic configuration diagram illustrating an example of the image forming apparatus of this embodiment.
[0054] Figure 2 This is a schematic configuration diagram illustrating an example of a processing cartridge that is mounted and dismounted in an image forming apparatus according to this embodiment.
[0055] Figure 3 This is a schematic diagram showing the cross-section of the toner particles in the electrostatic image developing toner of this embodiment. Detailed Implementation
[0056] The embodiments of the present invention will now be described. These descriptions and examples are for illustrative purposes only and do not limit the scope of the embodiments.
[0057] In this invention, the numerical range represented by “~” indicates the range of values recorded before and after “~” as the minimum and maximum values, respectively.
[0058] In this invention, the upper or lower limit of a numerical range recorded in stages can be replaced with the upper or lower limit of other numerical ranges recorded in different stages. Furthermore, the upper or lower limit of a numerical range recorded in this invention can be replaced with the values shown in the embodiments.
[0059] The term "step" in this invention includes not only independent steps, but also steps that can be clearly distinguished from other steps, as long as the desired purpose of the step can be achieved.
[0060] In this invention, while embodiments are described with reference to the accompanying drawings, the configuration of these embodiments is not limited to the configuration shown in the drawings. Furthermore, the sizes of the components in each figure are schematic, and the relative sizes of the components are not limited thereto.
[0061] In this invention, each component may contain two or more corresponding substances. In this invention, when referring to the amount of each component in a composition, if two or more substances conforming to each component are present in the composition, unless otherwise stated, it refers to the total amount of the two or more substances present in the composition.
[0062] In this invention, the particles corresponding to each component may comprise two or more types. When two or more particles corresponding to each component are present in the composition, unless otherwise stated, the particle size of each component refers to the value for a mixture of the two or more particles present in the composition.
[0063] In this invention, "electrostatic image developing toner" is also simply referred to as "toner" and "electrostatic image developing agent" is also simply referred to as "developer".
[0064] <Toning agents for electrostatic image development>
[0065] The colorant in this embodiment contains amorphous polyester resin, crystalline polyester resin, and CI pigment red 57:1. The Net intensity (N) of Mg element was determined by fluorescence X-ray analysis. Mg It is between 0.10 kcps and 0.40 kcps.
[0066] In this invention, "CI" is short for "Colour Index". The following shows the structural formula of CI Pigment Red 57:1.
[0067]
[0068] The color of the colorant in this embodiment is not limited. One example of the colorant in this embodiment is a magenta colorant.
[0069] The toner of this embodiment exhibits excellent transferability onto recording media with high water content. The mechanism is presumed to be as follows.
[0070] When toner particles are manufactured in an aqueous medium, CI Pigment Red 57:1, which has good affinity for water, readily aggregates near the surface of the toner particles. When CI Pigment Red 57:1 is present on the surface of the toner particles, charge leakage can easily occur, potentially leading to poor transfer. In image formation on recording media with high water content (such as embossed paper), poor transfer due to charge leakage in the toner becomes apparent.
[0071] Conversely, it is speculated that when Mg ions are present at the manufacturing site of the toner particles, the Ca ions constituting CI Pigment Red 57:1 will repel the Mg ions, and CI Pigment Red 57:1 will be dispersed inside the toner particles. As a result, it can be inferred that the amount of CI Pigment Red 57:1 present on the surface of the toner particles is relatively reduced, the leakage of charge from the toner is suppressed, and the transferability is improved.
[0072] Net intensity N of Mg element in colorant Mg A value less than 0.1 kcps indicates a low concentration of Mg ions at the manufacturing site of the colorant particles, resulting in insufficient Mg ion activity and poor colorant transferability. From this perspective, the net strength (N) of Mg is... Mg The value is 0.10 kcps or more, preferably 0.15 kcps or more, and more preferably 0.20 kcps or more.
[0073] Net intensity N of Mg element in colorant MgWhen the charge exceeds 0.4 kcps, excess charge in the colorant may lead to poor transfer due to charge leakage from the colorant. Based on this, the net strength N of Mg... Mg The value is 0.40 kcps or less, preferably 0.35 kcps or less, and more preferably 0.30 kcps or less.
[0074] The colorant of this embodiment contains CI Pigment Red 57:1, and therefore contains Ca ions, which constitute CI Pigment Red 57:1. In the colorant of this embodiment, the Net intensity (N) of Ca element, as measured by fluorescence X-ray analysis, is... Ca There are no particular limitations, but it is preferred to be 1.00 kcps or more and 3.00 kcps or less, more preferably 1.20 kcps or more and 2.50 kcps or less, and even more preferably 1.50 kcps or more and 2.00 kcps or less.
[0075] In this embodiment of the colorant, from the perspective of excellent transferability to recording media with relatively high water content, the Net intensity N of the Cl element was measured by fluorescence X-ray analysis. Cl Preferably, the concentration is 0.50 kcps or higher and 2.00 kcps or lower. It is speculated that the Cl ions present in the toner interact electrostatically with the Ca ions constituting CI Pigment Red 57:1, inhibiting the migration of CI Pigment Red 57:1 to the surface of the toner particles. However, if there are too many Cl ions, poor transfer may occur. Based on these considerations, in the toner of this embodiment, the Net strength N of the Cl element is... Cl Preferably, the concentration is 0.50 kcps or more and 2.00 kcps or less; more preferably, 0.70 kcps or more and 1.80 kcps or less; and even more preferably, 1.00 kcps or more and 1.50 kcps or less.
[0076] In the colorant of this embodiment, the Net intensity N of the Ca element... C Net strength N of Mg element Mg And the net strength N of Cl element Cl From the perspective of excellent transferability to recording media with high water content, a value of 0.50≦(N) is preferred. Mg +N Cl ) / N Ca ≤1.50, more preferably 0.80≦(N) Mg +N Cl ) / N Ca ≤1.30, further preferably 0.90≦(N) Mg +N Cl ) / N Ca ≤1.20.
[0077] Net strength N of Ca element Ca Net strength N of Mg element Mg Net strength N of Cl element Cl The determination method is as follows.
[0078] Approximately 5g of toner (including additives) was compressed using a compression molding machine under a load of 10t for 60 seconds to produce a disc with a diameter of 50mm and a thickness of 2mm. This disc was used as a sample for qualitative and quantitative elemental analysis using a scanning fluorescence X-ray analysis device (Rigaku ZSX Primus II) under the following conditions to determine the Net intensities (unit: kilo counts per second, kcps) for Ca, Mg, and Cl.
[0079] • Tube voltage: 40kV
[0080] Tube current: 75mA
[0081] • For cathode: rhodium
[0082] • Measurement time: 10 minutes
[0083] • Analytical diameter: 10mm
[0084] The mixing of Mg ions and Cl ions in colorants can be achieved, for example, by using magnesium chloride during the manufacture of colorant particles.
[0085] The details of the colorant in this embodiment will be described below.
[0086] The colorant in this embodiment is composed of colorant particles and, if necessary, additives.
[0087] [Toning agent granules]
[0088] Colorant particles are, for example, composed of an adhesive resin and, if necessary, colorants, release agents, and other additives.
[0089] -Adhesive resin-
[0090] The adhesive resin includes at least amorphous polyester resin and crystalline polyester resin.
[0091] The crystalline polyester resin in this invention refers to a polyester resin that does not exhibit a stepwise change in endothermic heat during differential scanning calorimetry (DSC) and has a distinct endothermic peak. Specifically, it refers to a polyester resin whose endothermic peak half-width is less than 10°C when measured at a heating rate of 10°C / min.
[0092] The amorphous polyester resin in this invention refers to: polyester resins whose endothermic peak half-width is greater than 10°C when measured at a heating rate of 10°C / min, polyester resins that show a step-like change in endothermic heat, or polyester resins for which no clear endothermic peak has been identified.
[0093] Amorphous polyester resin
[0094] Examples of amorphous polyester resins include condensation polymers of polycarboxylic acids and polyols. Commercially available or synthetic amorphous polyester resins can be used.
[0095] Examples of polycarboxylic acids include, for example, aliphatic dicarboxylic acids (such as oxalic acid, malonic acid, maleic acid, fumaric acid, citracic acid, itaconic acid, pentenic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (such as cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (such as terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), their anhydrides, or their lower (e.g., alkyl esters with 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferred as polycarboxylic acids.
[0096] In polycarboxylic acids, dicarboxylic acids can also be used in combination with tricarboxylic acids or more carboxylic acids that have a cross-linked or branched structure. Examples of tricarboxylic acids or more include trimellitic acid, benzopyrene, their anhydrides, or their lower (e.g., 1 to 5 carbon atoms) alkyl esters.
[0097] Polycarboxylic acids can be used alone or in combination of two or more.
[0098] Examples of polyols include aliphatic diols (such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (such as cyclohexanediol, cyclohexanediol, hydrogenated bisphenol A, etc.), and aromatic diols (such as ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, aromatic diols and alicyclic diols are preferred as polyols, and aromatic diols are more preferred.
[0099] As polyols, diols can also be used in combination with tri- or higher polyols that have cross-linked or branched structures. Examples of tri- or higher polyols include glycerol, trimethylolpropane, and pentaerythritol.
[0100] Polyols can be used alone or in combination of two or more.
[0101] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, more preferably 50°C or higher and 65°C or lower.
[0102] The glass transition temperature of amorphous polyester resin is determined by the DSC curve obtained by differential scanning calorimetry (DSC), or more specifically, by the "extrapolation of the glass transition onset temperature" as described in the method for determining the glass transition temperature in JIS K7121:1987 "Method for determination of transition temperature of plastics".
[0103] The weight-average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 to 1,000,000, more preferably 7,000 to 500,000. The number-average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 to 100,000. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 to 100, more preferably 2 to 60.
[0104] Weight-average molecular weight and number-average molecular weight were determined by gel permeation chromatography (GPC). For the molecular weight determination using GPC, a Tosoh GPC HLC-8120 GPC was used, along with a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent was employed. The weight-average and number-average molecular weights were calculated from these results using a molecular weight calibration curve prepared from monodisperse polystyrene standard samples.
[0105] Amorphous polyester resins are obtained by known manufacturing methods. Specifically, for example, they are obtained by: setting the polymerization temperature to 180°C or higher and 230°C or lower, and, if necessary, reducing the pressure within the reaction system while removing water or alcohol generated during condensation. If the raw monomers are insoluble or incompatible at the reaction temperature, a high-boiling-point solvent can be added as a dissolving agent to dissolve them. In this case, the condensation reaction is carried out while distilling off the dissolving agent. If monomers with poor compatibility are present in the copolymerization reaction, the monomers with poor compatibility can be pre-condensed with the acid or alcohol to which they are to be condensed, and then polycondensed with the main component.
[0106] As amorphous polyester resins, in addition to unmodified amorphous polyester resins, modified amorphous polyester resins can also be cited. Modified amorphous polyester resins refer to amorphous polyester resins containing linking groups other than ester bonds, or amorphous polyester resins formed by bonding resin components different from polyesters through covalent bonds or ionic bonds. Examples of modified amorphous polyester resins include resins that have undergone end modification by reacting an amorphous polyester resin with functional groups such as isocyanate groups introduced at its ends with an active hydrogen compound.
[0107] The proportion of amorphous polyester resin in all adhesive resins is preferably 60% by mass or more and 98% by mass, more preferably 65% by mass or more and 95% by mass, and even more preferably 70% by mass or more and 90% by mass.
[0108] Crystalline polyester resin
[0109] Examples of crystalline polyester resins include condensation polymers of polycarboxylic acids and polyols. Commercially available products or synthetic compounds can be used as crystalline polyester resins.
[0110] In order to facilitate the formation of crystalline polyester resins into crystalline structures, crystalline polyester resins preferably use condensates obtained from linear aliphatic polymeric monomers, rather than condensates obtained from polymeric monomers with aromatic rings.
[0111] Examples of polycarboxylic acids include aliphatic dicarboxylic acids (such as oxalic acid, succinic acid, glutaric acid, adipic acid, octanoic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), their anhydrides, or their lower (e.g., alkyl esters with 1 to 5 carbon atoms).
[0112] In polycarboxylic acids, dicarboxylic acids may also be used in combination with tricarboxylic acids or more that have a cross-linked or branched structure. Examples of tricarboxylic acids include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., alkyl esters with 1 to 5 carbon atoms).
[0113] As polycarboxylic acids, these dicarboxylic acids can be used in combination with dicarboxylic acids having sulfonic acid groups or dicarboxylic acids having olefinic double bonds.
[0114] Polycarboxylic acids can be used alone or in combination of two or more.
[0115] Examples of polyols include aliphatic diols (e.g., straight-chain aliphatic diols with 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosenediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols.
[0116] In polyols, diols can also be used in combination with tri- or higher alcohols that have cross-linked or branched structures. Examples of tri- or higher alcohols include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0117] Polyols can be used alone or in combination of two or more.
[0118] The content of aliphatic diols in polyols can be 80 mol% or more, preferably 90 mol% or more.
[0119] The melting temperature of the crystalline polyester resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, and even more preferably 60°C to 85°C.
[0120] The melting temperature of crystalline polyester resin is determined by the "melting peak temperature" described in the method for determining the melting temperature of JIS K7121:1987 "Method for determination of the transition temperature of plastics" based on the DSC curve obtained by differential scanning calorimetry (DSC).
[0121] The weight-average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0122] Crystalline polyester resins are obtained, for example, by known manufacturing methods, in the same manner as amorphous polyester resins.
[0123] As a crystalline polyester resin, a polymer of α,ω-linear aliphatic dicarboxylic acid and α,ω-linear aliphatic diol is preferred, considering its ease of forming a crystalline structure and its good compatibility with amorphous polyester resins.
[0124] As an α,ω-linear aliphatic dicarboxylic acid, it is preferable that the alkylene group connected to the two carboxyl groups has 3 to 14 carbon atoms. More preferably, the alkylene group has 4 to 12 carbon atoms, and even more preferably, the alkylene group has 6 to 10 carbon atoms.
[0125] Examples of α,ω-linear aliphatic dicarboxylic acids include succinic acid, glutaric acid, adipic acid, 1,6-hexanedicarboxylic acid (commonly known as octanoic acid), 1,7-heptanedicarboxylic acid (commonly known as azelaic acid), 1,8-octanedicarboxylic acid (commonly known as sebacic acid), 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid, with 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, 1,9-nonanedicarboxylic acid, and 1,10-decanedicarboxylic acid being preferred.
[0126] α,ω-linear aliphatic dicarboxylic acids can be used alone or in combination with two or more.
[0127] As an α,ω-linear aliphatic diol, it is preferable that the alkylene group connected to the two hydroxyl groups has 3 to 14 carbon atoms, more preferably 4 to 12 carbon atoms, and even more preferably 6 to 10 carbon atoms.
[0128] Examples of α,ω-linear aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 1,14-tetradecanediol, and 1,18-octadecanediol, with 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol being preferred.
[0129] α,ω-linear aliphatic diols can be used alone or in combination with two or more.
[0130] As a polymer of α,ω-linear aliphatic dicarboxylic acid and α,ω-linear aliphatic diol, from the perspective of easy formation of crystalline structure and good compatibility with amorphous polyester resin, a polymer selected from at least one of the group consisting of 1,6-hexanedicarboxylic acid, 1,7-heptanedicarboxylic acid, 1,8-octanedicarboxylic acid, 1,9-nonanedicarboxylic acid and 1,10-decanedicarboxylic acid and at least one of the group consisting of 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol and 1,10-decanediol is preferred.
[0131] The proportion of crystalline polyester resin in all adhesive resins is preferably 1% to 20% by mass, more preferably 2% to 15% by mass, and even more preferably 3% to 10% by mass.
[0132] ·Styrene-acrylic resin
[0133] Styrene-acrylic resin can be cited as an example of an adhesive resin. Styrene-acrylic resin is preferably an amorphous resin.
[0134] Examples of styrene monomers that constitute styrene-acrylic resins include styrene, α-methylstyrene, methylchlorostyrene, p-chlorostyrene, p-fluorostyrene, p-methoxystyrene, methyl tert-butoxystyrene, p-tert-butoxystyrene, p-vinylbenzoic acid, and p-methyl-α-methylstyrene. A single styrene monomer can be used, or two or more monomers can be used in combination.
[0135] Examples of (meth)acrylic monomers constituting styrene-acrylic resins include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)methacrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, isobornyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. A single (meth)acrylic monomer can be used alone, or two or more can be used in combination. In this invention, the term "(meth)acrylic acid" includes both "acrylic acid" and "methacryloyl group".
[0136] The preferred polymerization ratio of styrene monomers to (meth)acrylic monomers, based on mass, is styrene monomers:(meth)acrylic monomers = 70:30 to 95:5.
[0137] Styrene-acrylic resins can also have cross-linked structures. For example, styrene-acrylic resins with cross-linked structures can be manufactured by copolymerizing styrene monomers, (meth)acrylate monomers, and cross-linking monomers. There are no particular limitations on the cross-linking monomers, but (meth)acrylate compounds with two or more functional groups are preferred.
[0138] There are no particular restrictions on the production methods of styrene-acrylic resins; for example, solution polymerization, precipitation polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization can be used. Known operations (such as batch, semi-continuous, and continuous polymerization) can be applied during the polymerization reaction.
[0139] The proportion of styrene-acrylic resin in all adhesive resins is preferably 0% by mass or more and 20% by mass or less, more preferably 1% by mass or more and 15% by mass or less, and even more preferably 2% by mass or more and 10% by mass or less.
[0140] Other adhesive resins
[0141] Other adhesive resins include homopolymers of monomers such as olefinic unsaturated nitrile monomers (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ether monomers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketone monomers (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenone, etc.), and olefin monomers (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers.
[0142] Other examples of adhesive resins include epoxy resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, modified rosin, and other non-vinyl resins, mixtures of these non-vinyl resins with the aforementioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in their coexistence.
[0143] These adhesive resins can be used alone or in combination of two or more.
[0144] The content of the adhesive resin relative to the total amount of colorant particles is preferably 40% to 95% by mass, more preferably 50% to 90% by mass, and even more preferably 60% to 85% by mass.
[0145] -Coloring agents-
[0146] The colorant in this embodiment contains CI Pigment Red 57:1. The colorant in this embodiment may also contain other colorants besides CI Pigment Red 57:1. Other colorants include, for example, carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, sulfur-resistant orange, Voochug red, permanent red, bright carmine 3B, bright carmine 6B, DuPont oil red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose red, aniline blue, cyanine blue, oil-soluble blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate, etc.; acridine-based, xanthine-based, azo-based, benzoquinone-based, azazine-based, anthraquinone-based, thio-indigo-based, dioxazine-based, thiazine-based, azomethyl alkali-based, indigo-based, phthalocyanine-based, aniline black-based, polymethystine-based, triphenylmethane-based, diphenylmethane-based, thiazole-based, etc. These colorants can be used alone or in combination of two or more.
[0147] Colorants can be surface-treated as needed, or they can be used in combination with dispersants. Furthermore, two or more colorants can be used together.
[0148] The content of the colorant relative to the total amount of colorant particles is preferably 1% to 30% by mass, more preferably 3% to 15% by mass.
[0149] -Release agent-
[0150] Examples of release agents include: hydrocarbon waxes; natural waxes such as carnauba wax, rice bran wax, and candelilla wax; synthetic or mineral / petroleum-based waxes such as lignite wax; ester waxes such as fatty acid esters and lignite esters; and so on. Release agents are not limited to these.
[0151] As a release agent, ester waxes are preferred from the perspective that the release agent is finely dispersed during the manufacture of the colorant particles, thereby improving the dispersibility of CI pigment red 57:1. Examples of ester waxes include ester compounds formed between higher fatty acids having 10 or more carbon atoms and mono- or poly-ols, with a melting temperature of 60°C to 110°C (preferably 65°C to 100°C, more preferably 70°C to 95°C).
[0152] As an ester wax, ester compounds formed between higher fatty acids having 10 to 25 carbon atoms and mono- or polyols (preferably aliphatic alcohols having 8 or more carbon atoms) are preferred, and ester compounds formed between higher fatty acids having 16 to 21 carbon atoms and mono- or polyols (preferably aliphatic alcohols having 8 or more carbon atoms) are even more preferred.
[0153] Examples of ester waxes include ester compounds formed between higher fatty acids (decanoic acid, lauric acid, tetradecanoic acid, palmitic acid, stearic acid, arachidic acid, behenic acid, oleic acid, etc.) and alcohols (methanol, ethanol, propanol, isopropanol, butanol, octanol, lauryl alcohol, myristol, cetyl alcohol, stearyl alcohol, oleyl alcohol, etc. monohydric alcohols; glycerol, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, etc. polyhydric alcohols). Specifically, examples include carnauba wax, rice bran wax, candelilla wax, jojoba oil, wood wax, beeswax, insect wax, lanolin, and lignite ester wax.
[0154] The melting temperature of the release agent is preferably 50°C to 110°C, more preferably 60°C to 100°C.
[0155] The melting temperature of the release agent is determined by the "melting peak temperature" described in the method for determining the melting temperature in JIS K 7121:1987 "Method for determination of the transition temperature of plastics" based on the DSC curve obtained by differential scanning calorimetry (DSC).
[0156] The content of the release agent relative to the total amount of colorant particles is preferably 1% to 20% by mass, more preferably 5% to 15% by mass.
[0157] -Other Additives-
[0158] Other known additives include, for example, magnetic materials, charge control agents, and inorganic powders. These additives are contained in the colorant particles as internal additives.
[0159] -Characteristics of Toning Agent Particles-
[0160] Toner particles can be monolayer toner particles or so-called core / shell toner particles consisting of a core (core particle) and a coating layer (shell) covering the core.
[0161] The core / shell structured colorant particles can, for example, consist of a core and a coating layer, wherein the core is formed by including an adhesive resin and, if necessary, other additives such as colorants and release agents, and the coating layer is formed by including an adhesive resin.
[0162] The volume average particle size (D50v) of the colorant particles is preferably 2 μm or more and 10 μm or less, more preferably 4 μm or more and 8 μm or less.
[0163] The average particle size and particle size distribution of the colorant particles were measured using Coulter Multisizer II (manufactured by Beckman Coulter) and the electrolyte was measured using ISOTON-II (manufactured by Beckman Coulter).
[0164] During the determination, 0.5 mg to 50 mg of the test sample is added to 2 ml of a 5% aqueous solution of the surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant. This is then added to 100 ml to 150 ml of electrolyte.
[0165] The electrolyte containing the suspended sample was dispersed using an ultrasonic disperser for 1 minute. The particle size distribution of particles ranging from 2 μm to 60 μm was measured using a Coulter Multisizer II with 100 μm pores. 50,000 particles were sampled.
[0166] Relative to the particle size range (interval) defined by the measured particle size distribution, the cumulative distribution of volume and number is depicted from the small diameter side. The particle size at the cumulative 16% point is defined as the volumetric particle size D16v and the number particle size D16p, the particle size at the cumulative 50% point is defined as the volume average particle size D50v and the cumulative number average particle size D50p, and the particle size at the cumulative 84% point is defined as the volumetric particle size D84v and the number particle size D84p.
[0167] Using these values, the volumetric granularity distribution index (GSDv) is expressed as (D84v / D16v). 1 / 2 The number granularity distribution index (GSDp) was calculated to be (D84p / D16p). 1 / 2 Calculated.
[0168] The average roundness of the colorant particles is preferably 0.94 or more and 1.00 or less, more preferably 0.95 or more and 0.98 or less.
[0169] The average roundness of the toner particles is calculated using (equivalent circle circumference) / (circumference) [(circumference of a circle with the same projected area as the particle image) / (circumference of the particle projection image)]. Specifically, it is the value obtained by measuring using the method described below.
[0170] Toner particles, the object of measurement, are attracted and collected to form a flattened flow. A still image of the particles is obtained by momentarily flashing the particle image. The average roundness is calculated using a flow cytometry particle image analyzer (Sysmex FPIA-3000). The number of samples used to calculate the average roundness is 3500.
[0171] When the colorant contains additives, the colorant (developer) to be measured is dispersed in water containing a surfactant, and then subjected to ultrasonic treatment to obtain colorant particles with additives removed.
[0172] The colorant particles are preferably either the first colorant particles or the second colorant particles described below.
[0173] First colorant particles
[0174] When observing the cross-section of a colorant particle, the colorant particle contains at least two crystalline resin microregions that satisfy conditions (A), (B1), (C), and (D).
[0175] Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower.
[0176] Condition (B1): The major axis length of the crystalline resin microregion is 0.5 μm or more and 1.5 μm or less.
[0177] Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent described below is more than 60 degrees and less than 90 degrees. The tangent is the tangent at the junction where the extension meets the surface of the colorant particles.
[0178] Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.
[0179] Second colorant particles
[0180] When observing the cross-section of a colorant particle, the colorant particle contains at least two crystalline resin microregions that satisfy conditions (A), (B2), (C), and (D).
[0181] Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower.
[0182] Condition (B2): The ratio of the major axis length of the crystalline resin microregion in at least one of the two crystalline resin microregions to the maximum diameter of the colorant particle is more than 10% and less than 30%.
[0183] Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent below is more than 60 degrees and less than 90 degrees, and the tangent at the point where the extension meets the surface of the colorant particles.
[0184] Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.
[0185] The first colorant particles may or may not be the second colorant particles, but are preferably the second colorant particles.
[0186] The second colorant particles can be the first colorant particles, or they can be different from the first colorant particles, but preferably they are also the first colorant particles.
[0187] Figure 3 The diagram schematically shows the cross-section of a colorant particle. Figure 3 The symbols in the text represent: TN: colorant particles, Amo: amorphous resin, Cry: crystalline resin, L Cry : Major axis length of crystalline resin microregions, L T : Maximum diameter of colorant particles, θ A θ is the angle formed by the extension of the major axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction of the extension and the surface of the colorant particle). B The angle between the extensions of the long axes of the two crystalline resin microregions.
[0188] Toners containing either the first or second toner particles exhibit excellent transfer properties onto recording media with high water content. The reasons for this are speculated to be as follows.
[0189] In both the first and second colorant particles, at least two elliptical or needle-shaped crystalline resin microregions with large aspect ratios and long long axes extend from the surface of the colorant particle inwards and are arranged in a crisscross pattern (see reference). Figure 3 ).
[0190] It is speculated that due to the high affinity of CI Pigment Red 57:1 for crystalline resin, it penetrates into or around the microregions of the crystalline resin during the manufacture of toner particles. Therefore, it is hypothesized that within the toner particles, CI Pigment Red 57:1 is dispersed along the configuration of the crystalline resin microregions, suppressing the exposure of CI Pigment Red 57:1 on the surface of the toner particles. It is hypothesized that toner particles with suppressed surface exposure of CI Pigment Red 57:1 exhibit excellent transferability even when transferred to recording media with high water content.
[0191] In the first colorant particles, when the cross-section of the colorant particles is observed, at least two crystalline resin microregions (preferably at least three crystalline resin microregions) satisfy conditions (A), (B1), (C), and (D).
[0192] From the perspective of excellent transferability onto recording media with high water content, the first toner particles are preferably 40% or more, more preferably 70% or more, further preferably 80% or more, and particularly preferably 90% or more, relative to all toner particles. Ideally, the proportion of the first toner particles relative to all toner particles is 100%.
[0193] In the second colorant particles, when the cross-section of the colorant particles is observed, at least two crystalline resin microregions (preferably at least three crystalline resin microregions) satisfy conditions (A), (B2), (C), and (D).
[0194] From the perspective of excellent transferability onto recording media with high water content, the second toner particles are preferably 40% or more, more preferably 70% or more, further preferably 80% or more, and particularly preferably 90% or more, relative to all toner particles. Ideally, the proportion of the second toner particles relative to all toner particles is 100%.
[0195] Conditions (A), (B1), (B2), (C), and (D) each have a preferred range.
[0196] ·Condition(A)
[0197] From the perspective of excellent transferability to recording media with high water content, the aspect ratio of the crystalline resin micro-regions is 5 to 40, preferably 10 to 40.
[0198] The aspect ratio of a crystalline resin microregion refers to the ratio of its major axis length to its minor axis length (major axis length / minor axis length). The major axis length of a crystalline resin microregion refers to its maximum length. The minor axis length of a crystalline resin microregion refers to the maximum length in the direction orthogonal to the extension of its major axis length.
[0199] • Condition (B1)
[0200] From the perspective of excellent transferability to recording media with high water content, the long axis length of the crystalline resin microregion ( Figure 3 L in Cry The size is 0.5μm or more and 1.5μm or less, preferably 0.8μm or more and 1.5μm or less.
[0201] • Condition (B2)
[0202] From the perspective of excellent transferability to recording media with high water content, the long axis length of the crystalline resin microregion ( Figure 3 L in Cry ) relative to the maximum diameter of the colorant particles ( Figure 3 L in T The proportion of () is 10% to 30%, preferably 13% to 30%, and more preferably 17% to 30%.
[0203] The maximum diameter of a colorant particle refers to the maximum length of a straight line drawn from any two points on the outline of the cross-section of the colorant particle (the so-called major diameter).
[0204] • Condition (C)
[0205] From the perspective of excellent transferability onto recording media with high water content, the angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the toner particle (i.e., the outer edge of the toner particle) is considered. Figure 3 θ A The temperature is between 60 degrees and 90 degrees, preferably between 75 degrees and 90 degrees.
[0206] ·Condition(D)
[0207] From the perspective of excellent transferability onto recording media with high water content, the intersection angle between the extensions of the long axes of the two crystalline resin microregions is ( Figure 3 θ B The temperature should be between 45 degrees and 90 degrees, preferably between 60 degrees and 90 degrees.
[0208] • Method for observing the cross-section of colorant particles
[0209] Toner particles (or toner particles with added additives) were mixed and embedded in epoxy resin, which was then cured. The cured material was cut using an ultramicrotome (Leica Ultracut UCT) to produce thin sections with a thickness of 80 nm to 130 nm. The thin sections were stained with ruthenium tetroxide in a desiccator at 30 °C for 3 hours. STEM images of the stained thin sections were then obtained using a high-resolution field emission scanning electron microscope (FE-SEM, Hitachi S-4800) in transmission mode (accelerating voltage: 30 kV, magnification: 20,000x). When the images included cross-sections of toner particles of various sizes, cross-sections with a diameter greater than 85% of the volume average particle size of the toner particles were selected for observation. Here, the diameter of the toner particle cross-section refers to the maximum length of the straight line drawn from any two points on the outline of the toner particle cross-section (the so-called major axis).
[0210] In the image, amorphous resins, crystalline resins, and release agents are distinguished based on contrast and shape. Using ruthenium staining, amorphous resins (e.g., amorphous polyester resins) are stained the darkest, followed by crystalline resins (e.g., crystalline polyester resins), and release agents are stained the lightest. After adjusting the contrast, amorphous resins appear black, crystalline resins appear light gray, and release agents appear white.
[0211] Image analysis was performed on the micro-regions of the crystalline resin to determine whether the toner particles met conditions (A), (B1), (B2), (C), and (D). After determining the proportion of the first or second toner particles, 100 toner particles were observed, and the ratio of the number of first or second toner particles was calculated.
[0212] From the perspective of excellent transferability to recording media with high water content, the first and second toner particles preferably satisfy the following condition (E).
[0213] • Condition (E): When observing the cross-section of the toner particles, the release agent micro-region exists within a depth of 50 nm or more from the surface of the toner particles. That is, when observing the cross-section of the toner particles, the shortest distance between the release agent micro-region existing in the toner particles and the surface (i.e., the outer edge) of the toner particles is 50 nm or more.
[0214] Condition (E) means that the release agent micro-regions are not exposed on the surface of the toner particles. Once the release agent micro-regions are exposed on the surface of the toner particles, the additive will tend to adhere to the exposed parts of the release agent; if the release agent micro-regions are located at a depth of more than 50 nm from the surface of the toner particles, the additive will adhere to the surface of the toner particles in a near-uniform manner. As a result, transferability to recording media with high water content is excellent.
[0215] Condition (E) is confirmed by observing the cross-section of the colorant particles as described above.
[0216] From the perspective of excellent transferability to recording media with high water content, the proportion of the first toner particles satisfying condition (E) relative to all toner particles is preferably 40% or more, more preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and most preferably 100%.
[0217] From the perspective of excellent transferability to recording media with high water content, the proportion of the second toner particles satisfying condition (E) relative to all toner particles is preferably 40% or more, more preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and ideally 100%.
[0218] [Additives]
[0219] Examples of additives include inorganic particles. Examples of inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, and K2O·(TiO2). n Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.
[0220] The surface of inorganic particles used as additives can be hydrophobically treated. This hydrophobic treatment can be performed, for example, by impregnating the inorganic particles with a hydrophobic agent. There are no particular limitations on the hydrophobic agent; examples include silane-based coupling agents, silicone oils, titanate-based coupling agents, and aluminum-based coupling agents. They can be used alone or in combination. The amount of the hydrophobic agent is typically, for example, between 1 and 10 parts by mass relative to 100 parts by mass of the inorganic particles.
[0221] Other examples of additives include resin particles (such as polystyrene, polymethyl methacrylate, and melamine resin particles) and cleaning and activating agents (such as metal salts of higher fatty acids, such as zinc stearate, and particles of fluorine-based high molecular weight substances).
[0222] The amount of additive added is preferably 0.01% by mass or more and 5% by mass or less, more preferably 0.01% by mass or more and 2.0% by mass or less, relative to the colorant particles.
[0223] [Manufacturing method of colorant]
[0224] The colorant in this embodiment is obtained by adding an additive to the colorant particles after manufacturing the colorant particles.
[0225] Colorant particles can be manufactured using any of the following methods: dry manufacturing (e.g., mixing and pulverizing) or wet manufacturing (e.g., agglomeration and aggregation, suspension polymerization, dissolution suspension). There are no particular limitations on these methods, and well-known methods can be used. Among these, colorant particles can be obtained through agglomeration and aggregation.
[0226] Specifically, in the case of manufacturing colorant particles by agglomeration and merging, the colorant particles are manufactured through the following steps:
[0227] The steps for preparing an amorphous resin particle dispersion containing amorphous resin particles and a crystalline resin particle dispersion containing crystalline resin particles (resin particle dispersion preparation steps).
[0228] The step of agglomerating amorphous resin particles (and other particles if necessary) in an amorphous resin particle dispersion (or in a dispersion after mixing with other particle dispersions as needed) to form first aggregated particles (first aggregated particle forming step).
[0229] The agglomerated particle dispersion containing the first agglomerated particles is mixed with an amorphous resin particle dispersion and a crystalline resin particle dispersion (or the agglomerated particle dispersion containing the first agglomerated particles is mixed with a mixture of an amorphous resin particle dispersion and a crystalline resin particle dispersion), and agglomerated particles are formed by further attaching amorphous resin particles and crystalline resin particles to the surface of the first agglomerated particles. This operation is repeated more than twice to form the second agglomerated particles (the second agglomerated particle formation step).
[0230] The agglomerated particle dispersion containing the second agglomerated particles is mixed with an amorphous resin particle dispersion, and agglomerated in such a way that amorphous resin particles adhere to the surface of the second agglomerated particles to form the third agglomerated particles (the third agglomerated particle formation step); and
[0231] The step of heating the dispersion of agglomerated particles containing the third agglomerated particle to fuse / merge the agglomerated particles and form colorant particles (fusion / merging step).
[0232] The following details each step. The method for obtaining colorant particles containing colorant and release agent is described below; however, colorant and release agent are additives used as needed. Of course, other additives besides colorant and release agent can also be used.
[0233] -Preparation steps for resin particle dispersion-
[0234] Prepare an amorphous resin particle dispersion containing amorphous resin particles and a crystalline resin particle dispersion containing crystalline resin particles.
[0235] Colorants can also be included in amorphous resin particle dispersions. By dispersing a colorant while dispersing amorphous resin in a dispersion medium, an amorphous resin particle dispersion containing both amorphous resin particles and colorant particles can be prepared.
[0236] Resin particle dispersions are prepared, for example, by dispersing resin particles in a dispersion medium using a surfactant.
[0237] Examples of dispersion media used in resin particle dispersions include aqueous media. Examples of aqueous media include distilled water, ion-exchanged water, and alcohols. These media can be used alone or in combination of two or more.
[0238] Examples of surfactants include: anionic surfactants such as sulfate esters, sulfonates, phosphate esters, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. Among these, anionic and cationic surfactants are particularly noteworthy. Nonionic surfactants can also be used in combination with anionic or cationic surfactants. A surfactant can be used alone or in combination with two or more surfactants.
[0239] In resin particle dispersions, common methods for dispersing resin particles in a dispersion medium include using a rotary shear homogenizer, a ball mill with a media, a sand mill, and a bead mill. Depending on the type of resin particles, phase inversion emulsification can also be used to disperse the resin particles in the dispersion medium. Phase inversion emulsification involves dissolving the resin to be dispersed in a hydrophobic organic solvent that can dissolve the resin, adding an alkali to the organic continuous phase (O phase) for neutralization, and then adding an aqueous medium (W phase), thereby inverting the W / O phase to O / W, and dispersing the resin in particulate form in the aqueous medium.
[0240] The volume average particle size of the resin particles dispersed in the resin particle dispersion is preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and even more preferably 0.1 μm or more and 0.6 μm or less.
[0241] Regarding the volume average particle size of the resin particles, the particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., Horiba Manufacturing Co., Ltd. LA-700) was used. For the divided particle size range (segment), the cumulative volume distribution was plotted from the smallest particle size side, and the particle size at the cumulative 50% point relative to all particles was measured and taken as the volume average particle size D50v. The volume average particle size of particles in other dispersions was measured in the same way.
[0242] The resin particle dispersion contains preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 40% by mass or less.
[0243] Similar to resin particle dispersions, colorant particle dispersions and release agent particle dispersions are also prepared. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.
[0244] -Step 1: Formation of Aggregated Particles-
[0245] A dispersion of amorphous resin particles, a dispersion of colorant particles, and a dispersion of release agent particles are mixed. Then, the amorphous resin particles, colorant particles, and release agent particles are heterogeneously aggregated in the mixed dispersion to form first aggregated particles with a diameter similar to that of the target colorant particles and containing amorphous resin particles, colorant particles, and release agent particles. An amorphous resin particle dispersion containing both amorphous resin particles and colorant particles can be used as the amorphous resin particle dispersion.
[0246] Specifically, for example, a flocculant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to acidic (e.g., pH 2 or higher than 5). A dispersion stabilizer is added as needed, and then the mixture is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, the glass transition temperature of the resin particles -30°C to -10°C), causing the particles dispersed in the mixed dispersion to agglomerate and form the first agglomerated particles.
[0247] In the first step of forming aggregated particles, for example, a coagulant can be added at room temperature (e.g., 25°C) while the mixed dispersion is stirred using a rotary shear homogenizer, the pH of the mixed dispersion is adjusted to acidic (e.g., pH 2 or higher than 5), a dispersion stabilizer is added as needed, and then the mixture is heated.
[0248] Examples of flocculants include surfactants with polarity opposite to that of the surfactant contained in the mixed dispersion, inorganic metal salts, and metal complexes with a polarity of two or higher. When metal complexes are used as flocculants, the amount of surfactant required is reduced, and the charging characteristics are improved.
[0249] Additives that form complexes or similar bonds with the metal ions of the flocculant can be used as needed. Chelating agents are suitable as such additives.
[0250] Examples of inorganic metal salts include calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide; and so on.
[0251] Water-soluble chelating agents can be used as chelating agents. Examples of chelating agents include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; aminocarboxylic acids such as iminodiacetic acid (IDA), nitrotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA); and so on.
[0252] The amount of chelating agent added relative to 100 parts by weight of resin particles is preferably 0.01 parts by weight or more and 5.0 parts by weight or less, more preferably 0.1 parts by weight or more and less than 3.0 parts by weight.
[0253] -Step 2 of Aggregate Particle Formation-
[0254] The dispersion of the first aggregated particles is mixed with a dispersion of amorphous resin particles and a dispersion of crystalline resin particles. Alternatively, the dispersion of the first aggregated particles can be mixed with a mixture of a dispersion of amorphous resin particles and a dispersion of crystalline resin particles. Then, the amorphous resin particles and crystalline resin particles are agglomerated on the surface of the first aggregated particles in the dispersion containing the first aggregated particles, amorphous resin particles, and crystalline resin particles.
[0255] Specifically, for example, in the first aggregated particle formation step, when the first aggregated particles reach the target particle size, an amorphous resin particle dispersion and a crystalline resin particle dispersion are added, and heating is performed below the glass transition temperature of the amorphous resin particles. This agglomeration operation is repeated more than twice to form a second aggregated particle.
[0256] In the second aggregate particle formation step, it is preferable to add, for example, magnesium chloride to the dispersion to mix Mg ions and Cl ions in the colorant particles.
[0257] -Step 3: Formation of Aggregated Particles-
[0258] The dispersion of agglomerated particles containing the second agglomerated particles is mixed with a dispersion of amorphous resin particles. Then, the amorphous resin particles are agglomerated on the surface of the second agglomerated particles in the dispersion containing the second agglomerated particles and amorphous resin particles.
[0259] Specifically, for example, in the second aggregated particle formation step, when the second aggregated particles reach the target particle size, an amorphous resin particle dispersion is added, and heating is performed below the glass transition temperature of the amorphous resin particles. The pH of the dispersion is then adjusted to stop the aggregation process.
[0260] In the third step of forming aggregated particles, it is preferable to add, for example, magnesium chloride to the dispersion to mix Mg ions and Cl ions in the colorant particles.
[0261] -Merge / merge steps-
[0262] The dispersion of agglomerated particles containing the third agglomerated particle is heated to, for example, above the glass transition temperature of the amorphous resin particles (e.g., a temperature 10°C to 30°C higher than the glass transition temperature of the amorphous resin particles) to cause the agglomerated particles to fuse / merge, forming colorant particles.
[0263] After heating for fusion / merging, the temperature can be cooled to 30°C at a rate of 5°C / min to 40°C / min. This rapid cooling readily causes shrinkage of the toner particle surface, thus presumably leading to cracking from the interior of the toner particles towards the toner surface.
[0264] Next, the temperature is raised again at a rate of 0.1°C / min to 2°C / min, and maintained at a temperature above the melting temperature of the crystalline resin (-5°C) for at least 10 minutes. Then, the temperature is slowly cooled at a rate of 0.1°C / min to 1°C / min, thereby causing the crystalline resin microdomains to grow along the crack direction. The crystalline resin microdomains grow from the inside of the colorant particles toward the surface, thus satisfying the above conditions.
[0265] Furthermore, for example, when heating to above the melting temperature of the release agent during reheating, the likelihood of release agent micro-regions growing near the surface of the colorant particles increases. Therefore, the reheating temperature is preferably raised to a temperature above 5°C below the melting temperature of the crystalline resin and below the melting temperature of the release agent.
[0266] After the fusion / merging step, the toner particles formed in the solution are subjected to known washing, solid-liquid separation, and drying steps to obtain dried toner particles. Regarding the washing step, from a power efficiency perspective, displacement washing using ion-exchanged water can be fully implemented. Regarding the solid-liquid separation step, from a productivity perspective, methods such as vacuum filtration and pressure filtration can be implemented. Regarding the drying step, from a productivity perspective, methods such as freeze drying, airflow drying, fluidized bed drying, and vibrating fluidized bed drying can be implemented.
[0267] The colorant in this embodiment is manufactured, for example, by adding an additive to and mixing the obtained dried colorant particles. Mixing can be performed using, for example, a V-type mixer, a Henschel mixer, or a Rodier mixer. Furthermore, a vibrating screen, a pneumatic screen, or similar device can be used to remove coarse particles of the colorant as needed.
[0268] <Electrostatic Image Developer>
[0269] The electrostatic image developer of this embodiment contains at least the toner of this embodiment. The electrostatic image developer of this embodiment may be a single-component developer containing only the toner of this embodiment, or it may be a two-component developer formed by mixing the toner with a carrier.
[0270] There are no particular limitations on the carrier, and known carriers can be cited as examples. Examples of carriers include coated carriers in which resin is coated onto the surface of a core material formed of magnetic powder; magnetic powder dispersion carriers in which magnetic powder is dispersed and mixed in a matrix resin; and resin-impregnated carriers formed by impregnating porous magnetic powder with resin. Magnetic powder dispersion carriers and resin-impregnated carriers can also be carriers in which the constituent particles of the carrier are used as the core material and their surfaces are coated with resin.
[0271] Examples of magnetic powders include: magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and so on.
[0272] Examples of resins used for coating and matrix resins include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyethylene ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, pure silicone resins or their modifications comprising organosiloxane bonds, fluoropolymers, polyesters, polycarbonates, phenolic resins, epoxy resins, etc. Other additives, such as conductive particles, may be included in the coating and matrix resins. Examples of conductive particles include metals such as gold, silver, and copper, carbon black, titanium dioxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, potassium titanate, etc.
[0273] As a method of utilizing the surface of a resin-coated core material, examples include dissolving the coating resin and various additives (used as needed) in a suitable solvent and using the resulting coating layer forming solution. There are no particular limitations on the solvent; it can be selected considering the type of resin used, its coating suitability, etc.
[0274] Specific resin coating methods include: impregnation, in which the core material is impregnated in a coating layer forming solution; spraying, in which the coating layer forming solution is sprayed onto the surface of the core material; fluidized bed method, in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; kneading coating machine method, in which the core material of the carrier is mixed with the coating layer forming solution in a kneading coating machine, and then the solvent is removed; and so on.
[0275] The mixing ratio (mass ratio) of toner and carrier in the two-component developer is preferably toner:carrier = 1:100 to 30:100, more preferably 3:100 to 20:100.
[0276] <Image forming apparatus, image forming method>
[0277] The image forming apparatus and image forming method of this embodiment will be described.
[0278] The image forming apparatus of this embodiment includes: an image holder; a charging mechanism that charges the surface of the image holder; an electrostatic image forming mechanism that forms an electrostatic image on the charged surface of the image holder; a developing mechanism that stores an electrostatic image developer and develops the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer mechanism that transfers the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing mechanism that fixes the toner image transferred to the surface of the recording medium. Furthermore, the electrostatic image developer of this embodiment is used as the electrostatic image developer.
[0279] An image forming method (the image forming method of this embodiment) is implemented using the image forming apparatus of this embodiment. The method includes the following steps: a charging step, in which the surface of an image holder is charged; an electrostatic image forming step, in which an electrostatic image is formed on the charged surface of the image holder; a developing step, in which the electrostatic image formed on the surface of the image holder is developed into a toner image using the electrostatic image developer of this embodiment; a transfer step, in which the toner image formed on the surface of the image holder is transferred to the surface of a recording medium; and a fixing step, in which the toner image transferred to the surface of the recording medium is fixed.
[0280] The image forming apparatus of this embodiment is applicable to the following known image forming apparatuses: a direct transfer method apparatus that directly transfers a toner image formed on the surface of an image holder to a recording medium; an intermediate transfer method apparatus that first transfers a toner image formed on the surface of an image holder to the surface of an intermediate transfer body, and then transfers the toner image transferred to the surface of the intermediate transfer body to the surface of the recording medium a second time; an apparatus equipped with a cleaning mechanism for cleaning the surface of the image holder after the toner image is transferred but before charging; an apparatus equipped with a de-energizing mechanism for irradiating the surface of the image holder with de-energizing light to de-energize it after the toner image is transferred but before charging; and so on.
[0281] In the case where the image forming apparatus of this embodiment is an intermediate transfer method apparatus, the transfer mechanism, for example, uses a configuration having the following components: an intermediate transfer body that transfers a toner image to a surface; a primary transfer mechanism that transfers a toner image formed on the surface of an image holder to the surface of the intermediate transfer body in one step; and a secondary transfer mechanism that transfers the toner image transferred to the surface of the intermediate transfer body to the surface of a recording medium in a second step.
[0282] In the image forming apparatus of this embodiment, the portion including the developing mechanism may, for example, be a cartridge structure (processing cartridge) that is installed and removed from the image forming apparatus. As a processing cartridge, for example, a processing cartridge that stores the electrostatic image developer of this embodiment and has a developing mechanism is suitable.
[0283] The following shows an example of the image forming apparatus of this embodiment, but it is not limited thereto. In the following description, the main parts shown in the figures will be described, and the description of other parts will be omitted.
[0284] Figure 1 This is a schematic configuration diagram illustrating the image forming apparatus of this embodiment.
[0285] Figure 1 The image forming apparatus shown includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming mechanisms) of an electrophotographic method that outputs images of yellow (Y), magenta (M), blue (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged side-by-side at a predetermined distance from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K can be processing boxes that are mounted and removed from the image forming apparatus.
[0286] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (an example of an intermediate transfer body) 20 extends through each unit. The intermediate transfer belt 20 is wound around a drive roller 22 and a support roller 24, causing it to rotate in a direction from the first unit 10Y towards the fourth unit 10K. The support roller 24 is subjected to force in a direction separate from the drive roller 22 by springs (not shown), applying tension to the intermediate transfer belt 20 wound around both rollers. An intermediate transfer body cleaning device 30, opposite to the drive roller 22, is provided on the image holding side of the intermediate transfer belt 20.
[0287] Each toner (yellow, magenta, blue, black) is supplied to the developing apparatus (an example of a developing mechanism) 4Y, 4M, 4C, and 4K of each unit 10Y, 10M, 10C, and 10K, respectively. Each toner (yellow, magenta, blue, black) is stored in toner cartridges 8Y, 8M, 8C, and 8K.
[0288] Units 1 through 4, 10Y, 10M, 10C, and 10K, have the same structure and operation. Therefore, the first unit, 10Y, which forms the yellow image and is located on the upstream side of the intermediate transfer belt in the direction of travel, will be used as an example for explanation.
[0289] Unit 10Y has a photoreceptor 1Y that functions as an image holder. Around the photoreceptor 1Y are arranged in sequence: a charging roller (an example of a charging mechanism) 2Y, which charges the surface of the photoreceptor 1Y to a pre-set potential; an exposure device (an example of an electrostatic image forming mechanism) 3, which uses a laser line 3Y to expose the charged surface based on a color separation image signal to form an electrostatic image; a developing device (an example of a developing mechanism) 4Y, which supplies the charged toner to the electrostatic image for development; a primary transfer roller 5Y (an example of a primary transfer mechanism), which transfers the developed toner image onto an intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning mechanism) 6Y, which removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.
[0290] The primary transfer roller 5Y is positioned inside the intermediate transfer belt 20, opposite to the photosensitive element 1Y. Each unit's primary transfer rollers 5Y, 5M, 5C, and 5K are connected to a bias power supply (not shown) that applies a primary transfer bias voltage. The bias power supply changes the value of the transfer bias voltage applied to each primary transfer roller via a control unit (not shown).
[0291] The following explains the action of forming the yellow image in Unit 1, 10Y.
[0292] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600V to -800V using the charging roller 2Y.
[0293] Photoreceptor 1Y has good electrical conductivity (e.g., a volume resistivity of 1×10⁻⁶ at 20°C). -6 A photosensitive layer is deposited on a substrate (Ωcm or less). This photosensitive layer typically has high resistance (the resistance of common resins), but it has the property that the resistivity of the portion irradiated by the laser line changes when the laser line is irradiated. Therefore, based on yellow image data sent from a control unit (not shown), the laser line 3Y is irradiated by the exposure device 3 onto the surface of the charged photoreceptor 1Y. As a result, an electrostatic image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0294] An electrostatic image is an image formed on the surface of a photoreceptor 1Y by charging. It is a so-called negative latent image, which is formed as follows: the resistivity of the irradiated part of the photosensitive layer is reduced by using a laser line 3Y, causing the charged charge on the surface of the photoreceptor 1Y to flow; on the other hand, the charge remains in the part that is not irradiated by the laser line 3Y, thereby forming the negative latent image.
[0295] The electrostatic image formed on the photoreceptor 1Y rotates to a predetermined developing position as the photoreceptor 1Y rotates. At this developing position, the electrostatic image on the photoreceptor 1Y is developed into a toner image by the developing device 4Y and then visualized.
[0296] The developing apparatus 4Y stores an electrostatic image developer, for example, containing at least a yellow toner and a carrier. The yellow toner, inside the developing apparatus 4Y, becomes triboelectrically charged through agitation, acquiring a charge of the same polarity (negative polarity) as the charge on the photoreceptor 1Y, and is held on a developer roller (an example of a developer holder). The surface of the photoreceptor 1Y then passes through the developing apparatus 4Y, whereby the yellow toner electrostatically adheres to the de-charged latent image portion on the surface of the photoreceptor 1Y, and the latent image is developed using the yellow toner. The photoreceptor 1Y, with the yellow toner image formed, continues to rotate at a preset speed, conveying the developed toner image on the photoreceptor 1Y to a preset primary transfer position.
[0297] When the yellow toner image on the photoreceptor 1Y is transferred to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y. The electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, transferring the toner image on the photoreceptor 1Y onto the intermediate transfer belt 20. The applied transfer bias at this time has a (+) polarity opposite to the polarity (-) of the toner, for example, it is controlled to +10μA by a control unit (not shown) in the first unit 10Y.
[0298] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recycled using the photoreceptor cleaning device 6Y.
[0299] The primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K after 10M in Unit 2 is also controlled according to Unit 1.
[0300] In this way, the intermediate transfer belt 20, which has transferred the yellow toner image using the first unit 10Y, is sequentially transmitted through the second to fourth units 10M, 10C, and 10K, and the toner images of each color are transferred multiple times in an overlay manner.
[0301] The intermediate transfer belt 20, which has undergone multiple transfer of four toner images via units 1 to 4, reaches the secondary transfer section. This secondary transfer section comprises the intermediate transfer belt 20, a support roller 24 in contact with the inner surface of the intermediate transfer belt, and a secondary transfer roller (an example of a secondary transfer mechanism) 26 disposed on the image holding side of the intermediate transfer belt 20. Meanwhile, recording paper (an example of a recording medium) P is fed to the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 at a predetermined time by a supply member, and a secondary transfer bias is applied to the support roller 24. The applied transfer bias has the same polarity (-) as the toner, and the electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, transferring the toner image from the intermediate transfer belt 20 onto the recording paper P. The secondary transfer bias is determined based on the resistance detected by a resistance detection mechanism (not shown) that detects the resistance of the secondary transfer section, and the voltage is controlled accordingly.
[0302] Then, the recording paper P is fed into the pressing part (engaging part) of a pair of fixing rollers in the fixing device (an example of a fixing mechanism) 28, and the toner image is fixed on the recording paper P to form a fixed image.
[0303] Recording paper P used for transferring toner images can include, for example, ordinary paper used in photocopiers and printers using electrophotographic methods. In addition to recording paper P, other examples of recording media include OHP transparent film.
[0304] To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth, such as coated paper or art paper for printing, which are obtained by coating the surface of ordinary paper with resin or the like.
[0305] The recording paper P, which has been fixed with a color image, is sent to the discharge section, thus ending a series of color imaging actions.
[0306] <Processing Box>
[0307] The processing box of this embodiment will be described.
[0308] The processing box of this embodiment is a processing box that is installed and removed from the image forming apparatus. It has a developing mechanism that stores the electrostatic image developer of this embodiment and uses the electrostatic image developer to develop the electrostatic image formed on the surface of the image holder into a toner image.
[0309] The processing box of this embodiment is not limited to the above configuration, and may also be configured to include a developing mechanism and, if necessary, at least one of other mechanisms selected from an image holder, a charging mechanism, an electrostatic image forming mechanism, and a transfer mechanism.
[0310] The following shows an example of the processing box of this embodiment, but it is not limited thereto. In the following description, the main parts shown in the figures will be described, and the description of other parts will be omitted.
[0311] Figure 2 This is a schematic configuration diagram showing the processing box of this embodiment.
[0312] Figure 2 The processing cartridge 200 shown is constructed, for example, by using a housing 117 having a mounting rail 116 and an opening 118 for exposure to integrally combine and hold the photosensitive element 107 (an example of an image holder) with the charging roller 108 (an example of a charging mechanism), the developing device 111 (an example of a developing mechanism), and the photosensitive element cleaning device 113 (an example of a cleaning unit) surrounding the photosensitive element 107, thus forming an ink cartridge.
[0313] Figure 2 In the diagram, 109 represents an exposure device (an example of an electrostatic image forming mechanism), 112 represents a transfer device (an example of a transfer mechanism), 115 represents a fixing device (an example of a fixing mechanism), and 300 represents recording paper (an example of a recording medium).
[0314] Example
[0315] The embodiments of the present invention are described in detail below through examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise stated, "parts" and "%" are mass measurements.
[0316] Synthesis of Amorphous Polyester Resin (A)
[0317]
[0318] The above materials were added to a container equipped with a stirrer, thermometer, condenser, and nitrogen inlet pipe. Four parts of dibutyltin oxide catalyst were added, and nitrogen was introduced into the container to create an inert atmosphere. While maintaining the inert atmosphere, the temperature inside the container was increased, and the reaction was carried out for 12 hours at a temperature between 150°C and 230°C. Then, the pressure was slowly reduced while maintaining the temperature inside the container between 210°C and 250°C. This yielded an amorphous polyester resin (A) with a weight-average molecular weight of 10,500 and a glass transition temperature of 60°C.
[0319] <Preparation of an amorphous polyester resin particle dispersion (A1) containing CI Pigment Red 57:1>
[0320] 250 parts of amorphous polyester resin (A) and 50 parts of CI pigment red 57:1 (manufactured by DIC) were added to a Henschel mixer and mixed for 120 seconds at a screw speed of 600 rpm to obtain raw material (A). 200 parts of raw material (A) and 0.2 parts of 50% sodium hydroxide aqueous solution were fed into the feed inlet of a twin-screw extruder (TEM-58SS, manufactured by TOSHIBA MACHINE CO.,LTD). 4.1 parts of 48.5% sodium dodecyl diphenyl ether sulfonate aqueous solution (manufactured by Sanyo Chemical Industry Co., Ltd., Eleminol MON-7) were fed into the fourth barrel of the twin-screw extruder. The mixture was kneaded under the conditions of a barrel temperature of 95°C and a screw speed of 240 rpm. 150 parts by weight of ion-exchanged water at 95°C were fed into the 5th barrel of a twin-screw extruder, 150 parts by weight of ion-exchanged water at 95°C were fed into the 7th barrel, and 15 parts by weight of ion-exchanged water at 95°C were fed into the 9th barrel. The mixture was then kneaded under the condition that the average feed rate of raw material (A) was 200 kg / h, resulting in a resin particle dispersion containing resin particles with a volume average particle size of 180 nm. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 25%, yielding an amorphous polyester resin particle dispersion (A1) containing CI pigment red 57:1.
[0321] Synthesis of Crystalline Polyester Resin (B)
[0322] ·1,10-decanedicarboxylic acid: 241 parts
[0323] ·1,9-Nonadiol: 174 parts
[0324] The above-mentioned materials were added to a container equipped with a stirrer, thermometer, condenser, and nitrogen inlet pipe. After purging the gas in the container with dry nitrogen, 0.25 parts of tetrabutoxytitanium were added per 100 parts of the above-mentioned materials. The reaction was carried out under nitrogen gas flow at 170°C for 6 hours. Then, the temperature was raised to 210°C, the pressure inside the container was reduced to 3 kPa, and the reaction was carried out under reduced pressure with stirring for 13 hours. This yielded a crystalline polyester resin (B) with a weight-average molecular weight of 17200 and a melting temperature of 75°C.
[0325] <Preparation of Crystalline Polyester Resin Particle Dispersion (B1)>
[0326] 70 parts of ethyl acetate and 15 parts of isopropanol were added to a detachable flask and mixed. 100 parts of crystalline polyester resin (B) were then slowly added, and the mixture was stirred using a three-one motor to dissolve the resin, yielding an oil phase. 3 parts of a 10% ammonia solution were added dropwise to this oil phase, followed by 230 parts of deionized water at a dropping rate of 10 ml / min to induce phase inversion emulsification. Solvent removal was then performed under reduced pressure using an evaporator to obtain a resin particle dispersion containing resin particles with a volume average particle size of 165 nm. Deionized water was added to this resin particle dispersion to adjust the solid content to 25%, yielding a crystalline polyester resin particle dispersion (B1).
[0327] <Preparation of Styrene Acrylic Resin Particle Dispersion (C1)>
[0328]
[0329] The above materials were mixed and dissolved. The resulting mixture was then dispersed and emulsified in a flask with a surfactant solution containing 6 parts of a nonionic surfactant (Nonipol 400, manufactured by Sanyo Chemical Industry Co., Ltd.) and an anionic surfactant (NEOGEN SC, manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.) dissolved in 550 parts of ion-exchanged water. Next, while stirring the mixture in the flask, an aqueous solution containing 4 parts of ammonium persulfate dissolved in 50 parts of ion-exchanged water was added over 10 minutes. Following nitrogen purging, the mixture was heated in an oil bath while stirring until the contents reached 70°C. This temperature was maintained at 70°C for 5 hours to continue emulsion polymerization. This yielded a resin particle dispersion containing resin particles with a weight-average molecular weight of 30,000, a glass transition temperature of 52°C, and a volume-average particle size of 120 nm. Ion-exchanged water was added to this resin particle dispersion to adjust the solid content to 25%, yielding a styrene-acrylic resin particle dispersion (C1).
[0330] <Preparation of Release Agent Particle Dispersion (W1)>
[0331] • Ester wax (manufactured by Nippon Yushi Co., Ltd., WEP-8, melting temperature 79°C): 100 parts
[0332] • Anionic surfactant (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., NEOGEN RK): 1 part
[0333] • Ion-exchanged water: 350 parts
[0334] The above materials were mixed and heated to 100°C. After dispersion using a homogenizer (ULTRA-TURRAX T50 manufactured by IKA), the mixture was further dispersed using a pressure-discharge Gaulin homogenizer to obtain a release agent particle dispersion containing release agent particles with a volume average particle size of 200 nm. Ion-exchanged water was added to this release agent particle dispersion to adjust the solid content to 20%, resulting in release agent particle dispersion (W1).
[0335] <Example 1>
[0336] [Preparation of Toning Agent Granules]
[0337]
[0338] The above materials were placed in a round stainless steel flask. After adjusting the pH to 3.5 with 0.1N (0.1mol / L) nitric acid, an aqueous solution of magnesium chloride (6 parts dissolved in 30 parts of deionized water) was added. The mixture was dispersed at 30°C using a homogenizer (ULTRA-TURRAX T50, IKA), and then heated to 45°C in an oil bath, maintaining this temperature until the volume average particle size reached 4.5 μm.
[0339] Next, add 30 parts of amorphous polyester resin particle dispersion (A1) and 15 parts of crystalline polyester resin particle dispersion (B1), and then add 4 parts of the above-mentioned magnesium chloride aqueous solution, and maintain for 30 minutes. Add these three components every 30 minutes, for a total of 4 times.
[0340] Next, add 40 parts of amorphous polyester resin particle dispersion (A1) and 4 parts of the above-mentioned magnesium chloride aqueous solution, add 10 parts of 10% nitric acid triacetic acid metal salt aqueous solution (Chelest70, manufactured by Chelest Co., Ltd.), and adjust the pH to 9.0 using 1N sodium hydroxide aqueous solution.
[0341] Next, add 1 part of anionic surfactant (Tayca Power), and while continuing to stir, heat to 85°C at a rate of 0.05°C / min. After holding at 85°C for 3 hours, cool to 30°C at a rate of 15°C / min (first cooling). Then heat to 85°C again at a rate of 0.2°C / min, hold for 30 minutes, and then cool to 30°C at a rate of 0.5°C / min (second cooling).
[0342] The solid components were then filtered out, washed with ion-exchanged water, and dried to obtain colorant particles with a volume average particle size of 6.0 μm (1).
[0343] [Addition of external additives]
[0344] 100 parts of toner particles (1) were mixed with 1.5 parts of hydrophobic silica (manufactured by NIPPON AEROSIL Co., Ltd., RY50) and mixed for 30 seconds at a rotation speed of 10,000 rpm using a sample mill. The mixture was then sieved using a vibrating sieve with a mesh size of 45 μm to obtain toner (1). The volume average particle size of toner (1) was 6.0 μm.
[0345] [Net Strength N] Ca Net strength N Mg and Net strength N Cl [Determination]
[0346] Using the colorant (1) as a sample, qualitative and quantitative elemental analysis was performed using an X-ray analysis device (ZSX PrimusII manufactured by Rigaku Corporation) to determine the Net intensity (unit: kcps) of Ca, Mg and Cl elements.
[0347] [Determination of micro-regions in toner particles]
[0348] The micro-regions in the toner particles were determined according to the method described above. The toner of Example 1 contains toner particles that satisfy all conditions (A), (B1), (B2), (C), (D), and (E), and these toner particles account for more than 70% of all toner particles.
[0349] [Making of the carrier]
[0350] 500 parts of spherical magnetite powder (volume average particle size 0.55 μm) were stirred in a Henschel mixer, followed by the addition of 5 parts of a titanate-based coupling agent. The mixture was heated to 100 °C and stirred for 30 minutes. Then, 6.25 parts of phenol, 9.25 parts of 35% formaldehyde, 500 parts of magnetite particles treated with the titanate-based coupling agent, 6.25 parts of 25% ammonia, and 425 parts of water were added to a four-necked flask and stirred while reacting at 85 °C for 120 minutes. The mixture was then cooled to 25 °C, 500 parts of water were added, the supernatant was removed, and the precipitate was washed with water. The washed precipitate was dried under reduced pressure to obtain a support (M) with an average particle size of 35 μm.
[0351] [Mixing of toning agents and carriers]
[0352] The toner (1) and carrier (M) were added into a V-type mixer at a ratio of toner (1):carrier (M) = 5:95 (mass ratio) and stirred for 20 minutes to obtain developer (1).
[0353] <Examples 2-4>
[0354] The same process was carried out as for the preparation of colorant particles (1), except that the amount of magnesium chloride aqueous solution added was increased to prepare colorant particles (2) to (4) respectively.
[0355] The same process is followed as the preparation of toner (1) and developer (1), except that one of toner particles (2) to (4) is used instead of toner particles (1) to prepare toner particles (2) to (4) and developer (2) to (4).
[0356] <Comparative Example 1>
[0357] The same process is carried out as the preparation of colorant granules (1), except that an aluminum sulfate aqueous solution is prepared by dissolving 6 parts of aluminum sulfate in 30 parts of ion-exchanged water, and the aluminum sulfate aqueous solution is used instead of the magnesium chloride aqueous solution to prepare colorant granules (C1).
[0358] The same process is followed as for the preparation of toner (1) and developer (1), except that toner particles (C1) are used instead of toner particles (1) to prepare toner (C1) and developer (C1).
[0359] <Comparative Example 2>
[0360] The same process was carried out as for the preparation of colorant granules (1), except that the amount of magnesium chloride aqueous solution added was increased to prepare colorant granules (C2).
[0361] The same process is followed as for the preparation of toner (1) and developer (1), except that toner particles (C2) are used instead of toner particles (1) to prepare toner (C2) and developer (C2).
[0362] <Example 5>
[0363] [Preparation of Toning Agent Granules]
[0364]
[0365] The above materials were placed in a round stainless steel flask. After adjusting the pH to 3.5 with 0.1N (0.1mol / L) nitric acid, an aqueous solution of magnesium chloride (6 parts dissolved in 30 parts of deionized water) was added. The mixture was dispersed at 30°C using a homogenizer (ULTRA-TURRAX T50, IKA), and then heated to 45°C in an oil bath, maintaining this temperature until the volume average particle size reached 5.0 μm.
[0366] Next, 160 parts of the amorphous polyester resin particle dispersion (A1) were added, followed by 20 parts of the above-mentioned magnesium chloride aqueous solution, and the mixture was kept in this state until the average particle size reached the desired size. Then, 10 parts of a 10% azidotriacetic acid metal salt aqueous solution (Chelest70, manufactured by Chelest Co., Ltd.) were added, and the pH was adjusted to 9.0 using a 1N sodium hydroxide aqueous solution. Next, 1 part of anionic surfactant (Tayca Power) was added, and the temperature was increased to 85°C at a rate of 0.05°C / min while stirring. After maintaining the temperature at 85°C for 3 hours, the temperature was cooled to 30°C at a rate of 0.5°C / min. The solid components were then filtered out, washed with deionized water, and dried to obtain colorant particles (5) with a volume average particle size of 6.0 μm.
[0367] [Addition of external additives]
[0368] 100 parts of toner particles (5) were mixed with 1.5 parts of hydrophobic silica (manufactured by NIPPON AEROSIL Co., Ltd., RY50) and mixed for 30 seconds at a rotation speed of 10,000 rpm using a sample mill. The mixture was then sieved using a vibrating sieve with a mesh size of 45 μm to obtain toner (5). The volume average particle size of toner (5) was 6.0 μm.
[0369] [Net Strength N] Ca Net strength N Mg and Net strength N Cl [Determination]
[0370] Using the colorant (5) as a sample, qualitative and quantitative elemental analysis was performed using an X-ray analysis device (Rigaku ZSX PrimusII) to determine the Net intensity (unit: kcps) of Ca, Mg and Cl elements.
[0371] [Determination of micro-regions in toner particles]
[0372] The micro-regions in the toner particles were determined according to the method described above. The toner in Example 5 contained neither the first toner particles nor the second toner particles.
[0373] [Mixing of toning agents and carriers]
[0374] Add the toner (5) and carrier (M) to a V-type mixer at a ratio of toner (5):carrier (M) = 5:95 (mass ratio) and stir for 20 minutes to obtain developer (5).
[0375] <Performance Evaluation of Developers>
[0376] [Transferability]
[0377] Prepare a modified version of the Fuji Xerox "Docu Center Color 400" image forming device, store the developer in the developing unit, and place it in an environment with a temperature of 24°C and a relative humidity of 50% for 1 day.
[0378] As a recording medium, embossed paper (manufactured by Tokai Paper Co., Ltd., Lesac 66, 203GSM) was prepared and placed in an environment with a temperature of 28°C and a relative humidity of 85% for 1 day to adjust the humidity.
[0379] Ten rectangular patch images were printed on embossed paper after conditioning, at a temperature of 24°C and a relative humidity of 50%, with an image density of 1%. The tenth image was then observed. The transferability was graded according to the following criteria. G1 and G2 represent the practically permissible range.
[0380] G1: There is no color fading in the recessed areas of the embossed paper.
[0381] G2: Discoloration exists in the recesses of the embossed paper in an area of less than 5% of the image area.
[0382] G3: Discoloration exists in the recesses of the embossed paper, covering an area of more than 5% but less than 10% of the image area.
[0383] G4: Discoloration exists in the recesses of embossed paper, covering an area of more than 10% but less than 30% of the image area.
[0384] G5: Discoloration exists in the recesses of the embossed paper, covering an area of more than 30% of the image area.
[0385]
[0386] <Examples 101-129>
[0387] The same procedure was followed as for the preparation of the colorant particles (1), except that, in order to make the crystalline resin micro-regions and release agent micro-regions in the colorant particles have the characteristics shown in Tables 3 and 4, the type of release agent, the amount of resin particle dispersion used in the second agglomerated particle formation step, the amount of resin particle dispersion used in the third agglomerated particle formation step, and the fusion / merging step were adjusted to prepare colorant particles (101) to (129) respectively. The cooling rate of the first cooling, the holding temperature after reheating, and the cooling rate of the second cooling in the fusion / merging step were implemented as described in Table 2.
[0388] The same process is carried out as the preparation of toner (1) and developer (1), except that one of the toner particles (101) to (129) is used instead of the toner particles (1) to prepare toner (101) to (129) and developer (101) to (129).
[0389] Using colorants (101) to (129) as samples, qualitative and quantitative elemental analysis was performed using an X-ray analysis apparatus (Rigaku ZSX Primus II). The Net intensities (unit: kcps) of Ca, Mg, and Cl were determined. The colorants in Examples 101 to 129 were respectively: The Net intensity N of Ca was... Ca The net strength N of Mg is between 1.00 kcps and 3.00 kcps. Mg The net strength N of Cl element is between 0.10 kcps and 0.40 kcps. Cl The range is between 0.50 kcps and 2.00 kcps.
[0390] [Table 2]
[0391]
[0392]
[0393] [Table 4]
[0394]
[0395] The symbols in Tables 3 and 4 refer to the following items.
[0396] • First colorant particle A: Colorant particle that satisfies conditions (A), (B1), (C), and (D).
[0397] • First colorant particle B: Colorant particles that satisfy conditions (A'), (B1'), (C'), and (D').
[0398] Condition (A'): The aspect ratio of the crystalline resin microregions is 10 or higher and 40 or lower.
[0399] Condition (B1'): The major axis length of the crystalline resin microregion is 0.8 μm or more and 1.5 μm or less.
[0400] Condition (C'): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particles) is more than 75 degrees and less than 90 degrees.
[0401] Condition (D'): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 60 degrees and less than 90 degrees.
[0402] • Second colorant particle A: Colorant particles that satisfy conditions (A), (B2), (C), and (D).
[0403] • Second colorant particles B: Colorant particles that satisfy conditions (A'), (B2'), (C'), and (D').
[0404] Condition (A'): The aspect ratio of the crystalline resin microregions is 10 or higher and 40 or lower.
[0405] Condition (B2'): The ratio of the major axis length of the crystalline resin microregion to the maximum diameter of the colorant particles is more than 13% and less than 30%.
[0406] Condition (C'): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particles) is more than 75 degrees and less than 90 degrees.
[0407] Condition (D'): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 60 degrees and less than 90 degrees.
[0408] •AR: Aspect ratio of the micro-regions of crystalline resin.
[0409] ·L Cry : The length of the major axis of the crystalline resin microregion.
[0410] ·θA: The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent (the tangent is the tangent at the junction where the extension meets the surface of the colorant particles).
[0411] ·θB: The angle between the extensions of the major axes of the two crystalline resin microregions.
[0412] • Shortest distance: The shortest distance between the micro-area of the release agent and the surface (i.e., the outer edge) of the colorant particles.
[0413] ·Ester wax: WEP-5 manufactured by NOF Co., Ltd., melting temperature 85°C.
[0414] • Solid paraffin wax: HNP-0190 manufactured by Nippon Seika Co., Ltd., melting temperature 89℃.
[0415] • Polyethylene wax: Melting temperature 89℃.
Claims
1. A toner for electrostatic image development, comprising amorphous polyester resin, crystalline polyester resin, and CI pigment red 57:
1. The Net intensity (N) of Mg element in the electrostatic image developing toner was determined by fluorescence X-ray analysis. Mg For values between 0.10 kcps and 0.40 kcps, The Net intensity N of Ca, determined by fluorescence X-ray analysis. Ca The Net intensity (N) of Mg element determined by fluorescence X-ray diffraction. Mg And the Net intensity N of Cl element determined by fluorescence X-ray analysis Cl Satisfying 0.50≦(N) Mg +N Cl ) / N Ca A relationship of ≤1.50 The electrostatic image developing toner has toner particles that, when observed in cross-section, contain at least two crystalline resin microregions satisfying conditions (A), (B1), (C), and (D) below. Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower. Condition (B1): The major axis length of the crystalline resin microregions is 0.5 μm to 1.5 μm. Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent described below is between 60 and 90 degrees. This tangent is the tangent at the point where the extension intersects with the surface of the colorant particles. Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.
2. The toner for electrostatic image development as described in claim 1, wherein, The above Net strength N Mg The range is between 0.15 kcps and 0.35 kcps.
3. The toner for electrostatic image development as described in claim 1 or 2, wherein, The Net intensity N of Ca, determined by fluorescence X-ray analysis. Ca The range is between 1.00 kcps and 3.00 kcps.
4. The toner for electrostatic image development as described in claim 3, wherein, The above Net strength N Ca The range is between 1.20 kcps and 2.50 kcps.
5. The toner for electrostatic image development as described in claim 1 or 2, wherein, The Net intensity N of Cl element determined by fluorescence X-ray analysis Cl The range is between 0.50 kcps and 2.00 kcps.
6. The toner for electrostatic image development as described in claim 5, wherein, The above Net strength N Cl It is between 0.70 kcps and 1.80 kcps.
7. The toner for electrostatic image development as described in claim 1 or 2, wherein, The above Net strength N Ca The above Net strength N Mg And the aforementioned Net strength N Cl Satisfying 0.80≦(N) Mg +N Cl ) / N Ca The relationship is ≤1.
30.
8. The toner for electrostatic image development as described in claim 1 or 2, wherein, The aforementioned electrostatic image developing toner further contains a release agent, which comprises an ester compound formed between a mono- or polyol and a higher fatty acid having 10 to 25 carbon atoms.
9. The toner for electrostatic image development as claimed in claim 1 or 2, comprising toner particles that, when observed in cross-section, contain at least two crystalline resin microregions satisfying conditions (A), (B2), (C), and (D) below. Condition (A): The aspect ratio of the crystalline resin microregions is 5 or higher and 40 or lower. Condition (B2): The ratio of the major axis length of at least one of the two crystalline resin microregions to the maximum diameter of the colorant particle is more than 10% and less than 30%. Condition (C): The angle formed by the extension of the long axis of the crystalline resin micro-region and the tangent described below is between 60 and 90 degrees. This tangent is the tangent at the point where the extension intersects with the surface of the colorant particles. Condition (D): The angle between the extensions of the major axes of the two crystalline resin microregions is more than 45 degrees and less than 90 degrees.
10. The toner for electrostatic image development as described in claim 1 or 2, wherein, The aforementioned colorant particles contain a release agent. When the cross-section of the aforementioned colorant particles is observed, the micro-regions of the release agent exist within the interior at a depth of more than 50 nm from the surface of the aforementioned colorant particles.
11. The toner for electrostatic image development as described in claim 1 or 2, wherein, The content of the aforementioned colorant particles is more than 40% relative to all colorant particles.
12. The toner for electrostatic image development as claimed in claim 11, wherein, The content of the aforementioned colorant particles is more than 70% relative to all colorant particles.
13. An electrostatic image developer comprising the toner for electrostatic image development according to any one of claims 1 to 12.
14. A toner cartridge that is loaded and unloaded in an image forming apparatus, wherein the toner for electrostatic image development according to any one of claims 1 to 12 is stored.
15. A processing cartridge that is loaded and unloaded in an image forming apparatus, comprising a developing mechanism that stores the electrostatic image developer of claim 13, and using the electrostatic image developer to develop an electrostatic image formed on the surface of an image holder into a toner image.
16. An image forming apparatus comprising: Image holding volume; A charging mechanism that charges the surface of the image holder; An electrostatic image forming mechanism that forms an electrostatic image on the surface of the charged image holder; A developing mechanism that stores the electrostatic image developer of claim 13, and uses the electrostatic image developer to develop an electrostatic image formed on the surface of the image holder into a toner image. A transfer mechanism that transfers the toner image formed on the surface of the image holder to the surface of the recording medium; as well as A fixing unit fixes the toner image transferred to the surface of the recording medium.
17. An image forming method, comprising the following steps: The charging step involves charging the surface of the image holder. The electrostatic image formation step involves forming an electrostatic image on the surface of the charged image holder. In the development step, the electrostatic image formed on the surface of the image holder is developed into a toner image using the electrostatic image developer according to claim 13. The transfer step transfers the toner image formed on the surface of the image holder to the surface of the recording medium, and The fixing step involves fixing the toner image transferred to the surface of the recording medium.
Citation Information
Patent Citations
Toner and production method of toner
JP2017003990A
Toner and method for manufacturing the same
JP2019040024A
Toner for electrophotographic processes and electrostatic printing processes
CN107367912A
Magenta toner for electrostatic charge image development
CN108693724A
Electrostatic latent image developing toner
US20180259866A1